Prognostic Implication of Normalized Perfusion Scores in Patients with Known Coronary Artery Disease - Sarker, Azmal Kabir; Rahman, Hosne Ara; Naznin, Afroza; Sharmin, Samira; Iqbal, Khaled Mohammad; Hossain, Jamiul; Mahbub, Nazif; Ghosh, Debabrata; Yasmin, Farida (Bangladesh Journal of Nuclear Medicine, 2022)
Background: Normalized perfusion scores allow uniform interpretation of both 17 and 20-segment models. This is a report on the additional prognostic implications of normalized perfusion scores beyond their conventional roles in clinical management. Patients and methods: Patients undergoing gated SPECT myocardial perfusion imaging (GSMPI) with Adenosine stress from April 2018 to February 2019, were included in the study whose risk stratification and management recommendations were made using SS% and SD% respectively. The occurrence of cardiac events, quality of life (QOL), and management strategy were inquired about through a telephone interview in August 2020. An exploratory analysis was performed to find the significant interactions among imaging biomarkers, diabetes (DM), and the follow-up variables. Results: Imaging data from 17 patients (seven having DM) with a mean age of 49.8±10.4 were included. SS% was ≤14 in three patients and >14 in 14 patients. SD% was <10 in 12 patients and ≥ 10 in five patients. The SD% in DM patients suggested a similar extent of myocardial ischemia across the two SD% categories (p > 0.05). DM patients with a larger extent of ischemia had a greater stress-induced decline of LVEF (p = 0.029). SD% in DM patients with a stress-induced decline of LVEF was larger than those without a stress-induced decline of LVEF (p = 0.048). Follow-up data were available for 14 (82%) patients after a median interval of 26 months. Patients with non-improved QOL had larger perfusion defects in LCX territory, a higher proportion of cardiac soft events with SS% > 14, and CR despite an SD% < 10 (p < 0.05). Conclusions: Normalized perfusion scores in addition to their interaction with DM and stress-induced decline of LVEF, may have prognostic implications in the prediction of post-GSMPI QOL. Bangladesh J. Nuclear Med. 24(1&2): 18-27, 2021